Multicenter randomized controlled trial on Duration of Therapy for Thrombosis in Children and Young Adults (the Kids‐DOTT trial): pilot/feasibility phase findings. (11th August 2015) - Goldenberg, N. A.; Abshire, T.; Blatchford, P. J.; Fenton, L. Z.; Halperin, J. L.; Hiatt, W. R.; Kessler, C. M.; Kittelson, J. M.; Manco‐Johnson, M. J.; Spyropoulos, A. C.; Steg, P. G.; Stence, N. V.; et al.
Summary Background Randomized controlled trials (RCTs) on pediatric venous thromboembolism (VTE) treatment have been challenged by unsubstantiated design assumptions and/or poor accrual. Pilot/feasibility (P/F) studies are critical to future RCT success. Methods The Kids‐DOTT trial is a multicenter RCT investigating non‐inferiority of a 6‐week (shortened) versus 3‐month (conventional) duration of anticoagulation in patients aged < 21 years with provoked venous thrombosis. Primary efficacy and safety endpoints are symptomatic recurrent VTE at 1 year and anticoagulant‐related, clinically relevant bleeding. In the P/F phase, 100 participants were enrolled in an open, blinded‐endpoint, parallel‐cohort RCT design. Results No eligibility violations or randomization errors occurred. Of the enrolled patients, 69% were randomized, 3% missed the randomization window, and 28% were followed in prespecified observational cohorts for completely occlusive thrombosis or persistent antiphospholipid antibodies. Retention at 1 year was 82%. Interobserver agreement between local and blinded central determination of venous occlusion by imaging at 6 weeks after diagnosis was strong (k‐statistic = 0.75; 95% confidence interval [CI] 0.48–1.0). The primary efficacy and safety event rates were 3.3% (95% CI 0.3–11.5%) and 1.4% (95% CI 0.03–7.4%). Conclusions The P/F phase of the Kids‐DOTT trial has demonstrated the validity of vascular imaging findings of occlusion as a randomization criterion, and defined randomization, retention and endpoint rates to inform the fully powered RCT.